Short note: Correlated individual differences and choice prediction - Luke Lindsay (Games, 2011)
This note briefly summarizes the consequences of adding correlated individual differences to the best baseline model in the Games competition, I-SAW. I find evidence that the traits of an individual are correlated, but refining I-SAW to capture these correlations does not significantly improve the model's accuracy when predicting average behavior.
Keywords: 330; individual differences; choice prediction; I-SAW; modeling correlation